Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4236/ojrd.2013.34023
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Physiotherapy in a Web Browser, Feasibility Study

Abstract: In this paper, feasibility of web based breathing exercises for respiratory rehabilitation is examined. A system included visual guidance in a web browser and a microphone equipped headset for biofeedback and interaction. Feasibility was assessed in a controlled environment on 34 subjects with anxiety disorders that were not offered any help from the personnel. Weak points of comprehensibility were identified as applying headset (21%) and adhering to breathing exercises instructions (7%). No adverse events wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In [9] authors proposed using dedicated microphone to perform breathing exercises using conducting pursed lip breathing [10]. The performed experiments showed that conducting pursed lip breathing exercises by using an acoustic microphone in front of user's mouth is feasible and should be further researched.…”
Section: Imentioning
confidence: 98%
“…In [9] authors proposed using dedicated microphone to perform breathing exercises using conducting pursed lip breathing [10]. The performed experiments showed that conducting pursed lip breathing exercises by using an acoustic microphone in front of user's mouth is feasible and should be further researched.…”
Section: Imentioning
confidence: 98%
“…To detect exhalation through pursed lips, a microphone equipped headset was used [25]- [27]. Breathing controlled television was designed using Adobe Flash and YouTube API with the following algorithm (Figure 2 When exhalation through pursed lips is detected, a video playback begins.…”
Section: Methodsmentioning
confidence: 99%